Adaptive reuse practice for tower houses in the old city wall of Sana’a, Yemen / Laila Ahmed Mohammed Haidar - Ahmed Mohammed Haidar, Laila (2018)
The practice of adaptive reuse at the Old City of Sana'a, Yemen became noticeable, from the changes on the Tower Houses from residential to commercial. The practice unofficially established by the private owner with high intervention on the traditional materials and elements. Currently, the local authority conservation concerns only on the building exterior when major intervention on the interior materials and space layout.